Agger‐bullar classification (ABC) of the frontal sinus drainage pathway: validation in a preclinical setting. Issue 9 (30th March 2016) - Pianta, Luca; Ferrari, Marco; Schreiber, Alberto; Mattavelli, Davide; Lancini, Davide; Bottazzoli, Marco; Maroldi, Roberto; Rodella, Luigi Fabrizio; Ravanelli, Marco; Nicolai, Piero
Abstract : Background: The anatomy of structures surrounding the frontal sinus drainage pathway (FSDP) is extremely complex and challenging for endoscopic sinus surgeons. The anatomical nomenclature of this area reflects this complexity and lack of agreement regarding anatomical variants of this region is present in the literature. This work presents a new classification system of the air spaces surrounding the FSDP, called the agger‐bullar classification (ABC), and compares it with the most widely used anatomical classification of the frontoethmoidal region, the modified Bent and Kuhn classification (MBKC). Methods: Fourteen human heads underwent cone beam computed tomography (CT) scan and subsequently endoscopic dissection. Anatomical data were collected by 2 radiologists in consensus, an expert surgeon, and a novice surgeon. The radiologists filled the anatomical report after examining the CT scan, and the expert surgeon had both CT scan and endoscopic dissection available. A record of the dissection was obtained to allow the novice surgeon to compile the report. Interrater agreement regarding each variable of the classification systems was estimated through Cohen's kappa value. Cohen's kappa values of variables referring to the same anatomical subunit were matched to compare ABC with MBKC. Results: For both air spaces in front and behind the FSDP, interrater agreement values of the variables of the ABC were significantly higher than the corresponding variables of the MBKC. Conclusion: This preclinical study demonstrates the potential of the ABC system. Although the ABC may improve preoperative anatomical assessment of the frontoethmoidal area, validation in a clinical setting is required.